Micropropagation of Marsdenia brunoniana Wight & Arn. - A rare antidiabetic plant (Plant Tissue Culture and Biotechnology, 2010)
Shoot multiplication of M. brunoniana Wight & Arn. was achieved from the nodal explants of mature plants using MS with different concentrations and combina-tions of growth regulators. Maximum explant response and highest number of shoots per explant was obtained on MS medium fortified with 1.0 mg/l BAP. The highest degree of shoot proliferation was found to be 90%. The combination of BAP and Kn was also found to be effective for regeneration. The regenerated shoots were successfully rooted on MS supplemented with 0.5 mg/l NAA, after sequential hardening; survival rate was 90%.  Key words: Marsdenia brunoniana, Medinal plant, Micropropagation, Conservation D. O.I. 10.3329/ptcb.v20i1.5958 Plant Tissue Cult. & Biotech. 20(1): 7-12, 2010 (June)